Changes in expression of genes related to glucose metabolism in liver and skeletal muscle of rats exposed to acute hypoxia. Issue 7 (July 2020) - Hara, Yurie; Watanabe, Nakamichi
Abstract: The aim of this study was to determine changes in gene expression associated with glucose metabolism in the liver and soleus muscles of rats exposed to hypoxia to improve work capacity under high altitude conditions. Rats were divided into normobaric normoxia (control) and normobaric hypoxia (hypoxia) groups ( n = 7 each), and the hypoxia group was exposed to 10.5% oxygen for 90 min. Glucose metabolism-related gene expression was examined by real-time polymerase chain reaction. In the liver, the expression levels of the glucose utilization-related genes solute carrier family 2 member 1, glucokinase, and liver-type phosphofructokinase and the gluconeogenesis-related gene phosphoenolpyruvate carboxykinase 1 ( Pck1 ) were significantly increased upon hypoxic exposure. In contrast, gene expression in the soleus was unchanged, with the exception of Pck1 . The results suggest that under hypoxia, both glucose utilization and gluconeogenesis are accelerated in the liver, and liver glycogen is degraded to maintain blood glucose level. Abstract : Biochemistry; Molecular biology; Physiology; Organ System; glycolysis; Normobaric hypoxia; glycogen; gluconeogenesis